2016
DOI: 10.1155/2016/5403976
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Superabsorbent Polymers on the Hydraulic Parameters and Water Retention Properties of Soil

Abstract: Superabsorbent polymers (SAPs) are widely applied in dryland agriculture. However, their functional property of repeated absorption and release of soil water exerts periodic effects on the hydraulic parameters and water-retention properties of soil, and as this property gradually diminishes with time, its effects tend to be unstable. During the 120-day continuous soil cultivation experiment described in this paper, horizontal soil column infiltration and high-speed centrifugation tests were conducted on SAP-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 21 publications
2
18
0
2
Order By: Relevance
“…In this study, if a unique time‐dependent effect was not considered in the calculation method, the numerical experimental results indicated a pronounced error when the soil hydraulic parameters were decreased by 50–90%. As reported in previous studies, compared with the treatment without SAP application, significant decreases in the soil hydraulic parameters were observed, that is, up to 71.6% in the experiment carried by Han, Yu, et al () and 70–76% in the test performed by Liao et al (). Therefore, the time‐dependent effect of SAPs on soil hydraulic parameters should be fully considered when using the proposed calculation method to estimate RWU in response to SAPs.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In this study, if a unique time‐dependent effect was not considered in the calculation method, the numerical experimental results indicated a pronounced error when the soil hydraulic parameters were decreased by 50–90%. As reported in previous studies, compared with the treatment without SAP application, significant decreases in the soil hydraulic parameters were observed, that is, up to 71.6% in the experiment carried by Han, Yu, et al () and 70–76% in the test performed by Liao et al (). Therefore, the time‐dependent effect of SAPs on soil hydraulic parameters should be fully considered when using the proposed calculation method to estimate RWU in response to SAPs.…”
Section: Discussionsupporting
confidence: 69%
“…The parameters used in the calculations were as follows: time step 1000; distance step 0.125 (5 cm/40 cm); instrument precision w = 0.01; and the error threshold used in the iterative process was 1 × 10 −5 . The functional forms of D ( θ ) and K ( θ ) for the control group and of D ( θ , t ) and K ( θ , t ) for the SAP‐treated groups presented in a previous study (Liao et al, ) were used to calculate the RWU. The rates of soil surface evaporation measured in the controlled soil column experiment were as follows: CK: 0.026 cm·d −1 ; SFL group: 0.030 cm·d −1 ; SL group: 0.027 cm·d −1 ; and SH group: 0.029 cm·d −1 .…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…When soil is treated with SAP, its water retention properties are related to both porosity and the SAP's water absorbency. These results suggested that the adding of hydrogels into soil could obviously improve the water-retention capacity of soil and lessen the amount of water evaporation [35,38,39]. The trends of the curves suggest that the SAP improved the water retention properties of the treated soil during the early period.…”
Section: Water Retention Behavior In Soil-superabsorbent Polymermentioning
confidence: 86%